Co‐orchestration of acute kidney injury and non‐kidney organ failures in critically ill patients with cirrhosis. (23rd February 2021) - Maiwall, Rakhi; Pasupuleti, Samba Siva R.; Chandel, Shivendra S.; Narayan, Ashad; Jain, Priyanka; Mitra, Lalita Gouri; Kumar, Guresh; Moreau, Richard; Sarin, Shiv K.
Abstract: Background & Aims: Little is known on the course of acute kidney injury (AKI) and its relation to non‐kidney organ failures and mortality in critically ill patients with cirrhosis (CICs). Methods: We conducted a large prospective, single‐centre, observational study in which CICs were followed up daily, during the first 7 days of intensive care, collecting prespecified criteria for AKI, extrarenal extrahepatic organ failures (ERH‐OFs) and systemic inflammatory response syndrome (SIRS). Results: A total of 291 patients admitted to ICU were enrolled; 231 (79.4%) had at least one ERH‐OFs, 168 (58%) had AKI at presentation, and 145 (49.8%) died by 28 days. At day seven relative to baseline, 151 (51.8%) patients had progressive or persistent AKI, while the rest remained free of AKI or had AKI improvement. The 28‐day mortality rate was higher among patients with progressive/persistent AKI (74.2% vs 23.5%; P  < .001) or maximum stage 3 of AKI in the first week. Two‐level mixed logistic regression modelling identified independent baseline risk factors for progressive/persistent AKI, including 3 to 4 SIRS criteria, infections due to multidrug‐resistant bacteria (MDR), elevated serum bilirubin, and number of ERH‐OFs. Follow‐up risk factors included increases in bilirubin and chloride levels, and new development of 2 or 3 ERH‐OFs. Conclusions: Our results show that among CICs admitted to the ICU, the stage and course of AKI in the first week determines outcomes. Strategies combating MDR infections, multiorgan failure, liver failure and intense systemic inflammation could prevent AKI progression or persistence in CICs.